An Honourable U-Turn? Finland and New Europe after the End of the First World War - Vares Vesa (Sciendo, 2022)
The article deals with the situation of a small, newly- and uncertainly independent country that had a peculiar experience in the year 1918. The country had declared its independence in December 1917, had received the recognition from Soviet Russia, the Nordic countries, Germany and its allies, and France in January 1918. Almost simultaneously, it drifted to a civil war, in which both the Germans and the Russians participated. However, the Civil War was mainly a domestic concern, and the outcome was the defeat of an attempt at a socialist revolution and the victory of an extremely pro-German government that even elected a German king in Finland in October 1918. The project was never fulfilled, but the experience left an exceptional, pro-German mental heritage, to which the terms of the armistice of November 1918 was a shock. They were seen as unjust, revengeful and even petty—both by the Finnish “Whites” (non-socialists) and the “Reds” (socialists).
The Versailles Treaty in 1919 did not directly concern Finland. However, it might have done so in the question of Finnish borders, which was still partly unresolved—both in the west (a strife with Sweden over the Åland Islands) and in the east (ethnically Finnish Eastern Karelia). Moreover, the Allies were uncertain whether Finland should be considered Scandinavian or Baltic. Britain and the United States had not yet recognized Finland’s independence, so in order to secure independence and territorial integrity, the Finns had to adjust to the Allies’ demands and actively drive a Western-oriented policy. This was done for the same reason why the German orientation had been previously adapted—the threat of Russia and revolution—but it was psychologically strenuous for some political circles because they felt that there was an element of dishonorable opportunism to it. However, they could offer no alternative in a situation in which a newborn state had to secure its independence and legitimacy in New Europe, adjusting to disappointments and demands.